Growth and survival of river catfish Mystus nemurus (Cuvier & Valenciennes) larvae fed isocaloric diets with different protein levels during weaning - Eguia, R. V.; Kamarudin, M. S.; Santiago, C. B. (John Wiley & Sons Ltd, 2000)
The growth of river catfish Mystus nemurus (Cuvier & Valenciennes) larvae fed four isocaloric diets (4200 kcal kg−1) with different protein levels during weaning was determined. Diets containing 45, 50, 55, and 60% protein were formulated by linear programming using amino acid profiles based on that of 2-day-old river catfish larvae. Artificial diets were fed to the larvae beginning at day 5 after being initially fed Artemia nauplii for 4 days. The larvae thrived solely on artificial diets from day 8 to day 16. On the other hand, the control larvae were fed Artemia nauplii from day 1 to day 16. Results of the feeding trial showed that growth and survival of M. nemurus larvae given the diet containing 60% protein were high and comparable to those of the larvae given only live food (control). Larvae fed the 55% protein diet had significantly lower growth and survival than the larvae on the control and 60% diets but significantly higher growth and survival rates than did larvae fed with 45 and 50% protein diets. Carcass moisture and total lipids after 16 days of feeding did not differ significantly (P > 0.05), but body protein increased with increasing dietary protein. Body protein of the control larvae was similar to that of larvae given the 60% protein diet.